A nationwide register‐study of healthcare utilisation in the year preceding a colorectal cancer recurrence diagnosis. (22nd July 2021) - Rasmussen, Linda Aagaard; Jensen, Henry; Falborg, Alina Zalounina; Iversen, Lene Hjerrild; Vedsted, Peter
Abstract: Objective: To analyse healthcare utilisation in colorectal cancer (CRC) survivors in the 12 months preceding a diagnosis of CRC recurrence. Methods: This register‐based cohort study included curatively treated survivors of CRC diagnosed in 2008–2018. Survivors with CRC recurrence were matched 1:5 with recurrence‐free survivors. We estimated the monthly frequency of healthcare utilisation before the recurrence diagnosis and a corresponding index date assigned to the matched population. A regression model was used to compare healthcare utilisation between groups. Results: We included 3045 survivors with recurrence and 15, 225 recurrence‐free survivors. At study entry, both groups had on average one contact per month to general practice. Compared with recurrence‐free survivors, survivors with recurrence had more contacts to general practice from 10 months before the diagnosis and more haemoglobin measurements from 4 months before the diagnosis. They had more contacts to hospitals and follow‐up clinics from 7 months before the diagnosis and more diagnostic investigations from 2 months before the diagnosis. Conclusion: General practitioners have regular contact with CRC survivors and are involved in detecting recurrence. The increased number of contacts in the months before the rise in diagnostic investigations indicates an opportunity to expedite referral to diagnostics and the diagnosis of CRC recurrence.